Statistical study on the ecological conception of people about the importance of bees (Revista Brasileira Multidisciplinar, 2021)
Bees are important insects for the environment, known for their role in pollination. They appeared in the Cretaceous, are related to the appearance of the first flowering plants and are essential for food production. Given this information, knowing people's perception of the ecological importance of these invertebrates is essential for their protection and implementation of awareness-raising efforts. Thus, the objective was to assess people's perception of the ecological importance of bees. The survey was carried out using a Google Forms form, sent to participants through different social networks. 256 people of both sexes were interviewed, with ages between 15 and 70 years old and with different educational levels. People of both sexes, aged between 21 and 50, with different levels of education, had a greater understanding of the importance of bees
Keywords: Ecosystem; Statistical Study; Interview; Pollination